Teaching of expressive repertoire to children who are users of Cochlear implants: A literature review - Cravo, Felipe Augusto Monteiro [UNESP]; Almeida-Verdu, Ana Cláudia Moreira [UNESP]; Silva, Leandra Tabanez Do Nascimento; Moret, Adriane Lima Mortari (My University, 2018)
The aims of this research were (a) to verify the quantity of scientific productions that described procedures of teaching of expressive repertoire, according to Skinner’s verbal categories (1957), to children with cochlear implants; (b) to characterize their methods, considering participants, stimuli, materials and experimental design used; (c) to identify manipulated independent variable and dependent measured variable. The methodology followed the PRISMA model for literature reviews and meta-analyzes; the search was done in the Web of Science with the descriptors and bullet points: “Cochlear Implant”, [and] “Children” [and] “Language”, [and] “Teaching”. We found 39 papers and, after applying the exclusion criteria, we obtained 12 papers for analysis. Among them, eight papers described methodologies of expressive repertoire teaching. The data pointed out that a concentration of international publications between the years 2012 and 2015. The intraverbal operant has been the major target of the interventions found, followed by tact and textual ones. More than 50% of the studies made use of single-subject experimental designs, corroborating with the indications about the importance of this type of design for research in health and education. National publications were not found, although there is a strong line of research in the country. In order to avoid this situation, it is necessary to insert intentionally the research that is known to the set of researches found through systematic reviews. Synthesizing publications that present teaching methodologies to this population may favor Special Education professionals in the elaboration of their interventions and curricula.
Ensino de repertórios expressivos a crianças usuárias de implante Coclear: Uma revisão de literatura
Keywords: Behavior analysis; Cochlear implant; Special education